Coseismic fault-slip distribution of the 2019 Ridgecrest Mw6.4 and Mw7.1 earthquakes - Yang Gao (Nature Portfolio, 2021)
Abstract The 2019 Ridgecrest, California seismic sequence, including an Mw6.4 foreshock and Mw7.1 mainshock, represent the largest regional seismic events within the past 20 years. To obtain accurate coseismic fault-slip distribution, we used precise positioning data of small earthquakes from January 2019 to October 2020 to determine the dip parameters of the eight fault geometry, and used the Interferometric Synthetic Aperture Radar (InSAR) data processed by Xu et al. (Seismol Res Lett 91(4):1979–1985, 2020) at UCSD to constrain inversion of the fault-slip distribution of both earthquakes. The results showed that all faults were sinistral strike-slips with minor dip-slip components, exception for dextral strike-slip fault F2. Fault-slip mainly occurred at depths of 0–12 km, with a maximum slip of 3.0 m. The F1 fault contained two slip peaks located at 2 km of fault S4 and 6 km of fault S5 depth, the latter being located directly above the Mw7.1hypocenter. Two slip peaks with maximum slip of 1.5 m located 8 and 20 km from the SW endpoint of the F2 fault were also identified, and the latter corresponds to the Mw6.4 earthquake. We also analyzed the influence of different inversion parameters on the fault slip distribution, and found that the slip momentum smoothing condition was more suitable for the inversion of the earthquakes slip distribution than the stress-drop smoothing condition.